'Genetic resources', an analysis of a multifaceted concept. (June 2018) - Deplazes-Zemp, Anna
Abstract: 'Genetic resources' is a key concept of the Convention on Biological Diversity (CBD) and the Nagoya Protocol (NP). However, the term was coined to describe value in biodiversity and create an incentive for its protection and is thus of practical relevance for biological conservation beyond the legal context. The scope of this concept is also of interest to researchers, who may be unsure for which types of analysis they are legally and ethically expected to enter access and benefit sharing (ABS) negotiations. This article presents a biologically informed analysis, which leads to an understanding of 'genetic resources' that considers various associations and implications of this notion, such as its relation to biodiversity and the role that intellectual property rights (IPR) play in the discourse. The aim is to provide a coherent, consistent and comprehensive understanding of the concept that can integrate and explain these aspects and consider both classical and novel ways of using genetic resources. Based on the biological function of genetic resources and an analysis of how they are currently used and valued, this article argues that genetic resources are a particular type of natural resource that is informational rather than tangible. This interpretation clearly identifies utilising digital genomic sequences as a form of using genetic resources. However, the article also discusses regulatory exceptions for certain utilisations of genetic resources and it mentions the possibility of treating digital sequences as such an exception. Highlights: 'Genetic resources' is a multifaceted concept with interdisciplinary connotations. The term 'genetic resources' refers to instrumental value in biodiversity. In many respects, genetic resources are different from other natural resources. Their biological foundation reveals the informational nature of genetic resources. The resource value of genetic resources lies in the information they carry.